2016
DOI: 10.3389/fmicb.2016.00090
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure of Activated Sludge in Treatment Plants with Different Wastewater Compositions

Abstract: Activated sludge (AS) plays a crucial role in the treatment of domestic and industrial wastewater. AS is a biocenosis of microorganisms capable of degrading various pollutants, including organic compounds, toxicants, and xenobiotics. We performed 16S rRNA gene sequencing of AS and incoming sewage in three wastewater treatment plants (WWTPs) responsible for processing sewage with different origins: municipal wastewater, slaughterhouse wastewater, and refinery sewage. In contrast to incoming wastewater, the taxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(86 citation statements)
references
References 47 publications
3
82
0
1
Order By: Relevance
“…The microbial profile of influent sewage does not remain constant through the depuration process; although bacteria clearly predominate over the other dominia throughout treatment processes (Yu and Zhang 2012). The selection of the predominant families of bacteria during the depuration process is mostly determined by the chemical composition of the incoming waters and type of treatment, and they are very different from one report to another (Sanapareddy et al 2009;Yu and Zhang 2012;Cai et al 2014;Shchegolkova et al 2016). The composition of effluents, which are released into the receiving waters, usually reflects the composition of the activated sludge (Cai et al 2014).…”
Section: Effluent From Wastewater Treatment Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial profile of influent sewage does not remain constant through the depuration process; although bacteria clearly predominate over the other dominia throughout treatment processes (Yu and Zhang 2012). The selection of the predominant families of bacteria during the depuration process is mostly determined by the chemical composition of the incoming waters and type of treatment, and they are very different from one report to another (Sanapareddy et al 2009;Yu and Zhang 2012;Cai et al 2014;Shchegolkova et al 2016). The composition of effluents, which are released into the receiving waters, usually reflects the composition of the activated sludge (Cai et al 2014).…”
Section: Effluent From Wastewater Treatment Facilitiesmentioning
confidence: 99%
“…; Shchegolkova et al . ). The composition of effluents, which are released into the receiving waters, usually reflects the composition of the activated sludge (Cai et al .…”
Section: Introductionmentioning
confidence: 97%
“…The upper bound for pathogenic concentrations, ca. 10 6 cells/ml, has been reported for the sediment-water interface (Travers et al, 2009) and in a sewage spill scenario (Shchegolkova et al, 2016). The total concentration of all bacterial species, of which the focal pathogen was a subset, was assumed constant at 10 6 cells/ ml Kramer et al, 2013).…”
Section: Pathogens On Aggregatesmentioning
confidence: 99%
“…In either case, the nucleotide sequences of millions of DNA fragments are determined, and then computational analyses are used to identify and quantify all of the organisms (or genes) as long as they are found within already extensive and growing databases (Gilbert and DuPont, 2011;Vanwonterghem et al, 2014). MGA is developing in the academic realm as a powerful approach to gain insight into processes that are of fundamental interest to the WWTP community (Ibarbalz et al, 2016;Jiang, et al, 2016;Sharma et al, 2012;Shchegolkova, 2016;Yang, et al, 2014). Research has shown, for example, that reactor populations can vary over time, at least in part due to changes in climatic and operational conditions (Ju et al, 2014;Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%